IMPLEMENTASI SISTEM PAKAR UNTUK MEMPREDIKSI POTENSI KECANDUAN MAHASISWA TERHADAP GAME ONLINE MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Larasati, Yustika; Budi, Akhmad (Jurnal Informatika dan Bisnis, 2022)
Technology development in Indonesia is very fast. There are many benefits of technology, one of which is for entertainment needs. Playing online games is a form of entertainment need. Apart from having benefits, online games also have a negative impact on life, namely that a person can become addicted. To ensure that someone has an addiction, that person must go to an expert, namely a psychologist. However, to do counseling requires a lot of money, so this early detection system is made for people who like to self-diagnose themselves addicted to online games. Expert system is a form of Artificial Intelligence. Implementation of an expert system can be collaborated with the forward chaining method. This research uses the waterfall development method. The data taken for this study were obtained through questionnaires and interviews. The data will be used in the form of a knowledge base which contains 6 aspects consisting of 40 lists of symptoms along with their indicators and 5 solutions obtained from interviews with a human expert. Decision making in an expert system will be processed using a formula that has been given by human experts. The results of this study are the percentage of potential addictions to online games and solutions obtained by answering knowledge base statements. The expert system produced by this researcher can be used as an initial assessment that makes it easier for psychologists to make diagnoses. Keywords : Expert System, Addiction, Game Online, Forward Chaining